Hubungan Stres dengan Stomatitis Aftosa Rekuren pada Mahasiswa Program Studi Pendidikan Dokter Gigi Universitas Sam Ratulangi - Wowor, Yosef P.; Munayang, Herdy; Supit, Aurelia (e-GiGi, 2019)
Abstract: Recurrent aphtosa stomatitis (RAS) or aphthous ulcer on the oral mucosa can be triggered by several predisposing factors, inter alia stress. This study was aimed to determine the relationship between stress and RAS among students of Dentistry Study Program of Sam Ratulangi University. This was an analytical study with a cross sectional design. Samples were obtained by using total sampling method. There were 64 students as respondents. This study was conducted by examination of the oral cavity of the respondents, and filling the SAR question list as well as the perceived stress scale (PSS) questionnaire. The results showed that 48% of respondents experienced RAS and 51.6% did not. Moreover, 25% of respondents experienced mild stress, 45.3% moderate stress, and 29.7% severe stress. The chi-square test showed a p-value of 0.000. In conlusion, there was a significant relationship between stress and recurrent aphthous stomatitis among students at Dentistry Study Program of Sam Ratulangi University.Keywords: recurrent aphthous stomatitis, stress levelÂ Abstrak: Stomatitis aftosa rekuren (sar) atau ulkus aftosa pada mukosa mulut yang bersifat rekuren dapat dipicu oleh beberapa faktor predisposisi salah satunya stres. Tujuan penelitian ini untuk mengetahui hubungan stres dengan stomatitis aftosa rekuren pada mahasiswa Program Studi Pendidikan Dokter Gigi Universitas Sam Ratulangi. Jenis penelitian ialah analitik dengan desain potong lintang. Pengambilan sampel menggunakan metode total sampling seluruh mahasiswa di Program Studi. Terdapat total 64 mahasiswa sebagai responden penelitian. Penelitian dilakukan melalui pemeriksaan rongga mulut, serta pengisian daftar pertanyaan SAR dan kuesioner perceived stress scale (PSS). Hasil penelitian menunjukkan bahwa 48% responden mengalami SAR dan 51,6% yang tidak mengalami SAR. Selain itu, 25% responden mengalami tingkat stres ringan, 45,3% sedang, dan 29,7% berat. Hasil analisis uji chi-square menunjukkan nilai p=0,000. Simpulan penelitian ini ialah terdapat hubungan bermakna antara stres dengan stomatitis aftosa rekuren pada mahasiswa Program Studi Pendidikan Dokter Gigi Universitas Sam Ratulangi.Kata kunci: stomatitis aftosa rekuren, tingkat stress